PELATIHAN BRANDING DAN PRODUCT PACKAGING MANAGEMENT MASYARAKAT PESISIR PASURUAN (RENGGINANG UDANG UCIYA) SEBAGAI POTENSI UTAMA USAHA KECIL MENENGAH (UKM) KHAS DESA RACI, BANGIL PASURUAN - Aris Setiawan (LPPM Universitas Yudharta Pasuruan, 2018)
Alternative Real Work Lecture Program (Alternative KKN) which has been planned can run well even though there are activities that are not carried out according to the time planned but changed schedule due to weather factors and unplanned activity factors of the Program objectives. Not only that another obstacle arises because of lack of funds to carry out planned activities. Forming students to become more mature in addressing existing problems and understanding how to live in society. In addition, it can form an independent personality and is responsible for their duties and functions and forms the spirit of leadership.